The presence of the Orthodox Churches and the Eastern-rite Catholic Churches in the III Extraordinary General Assembly of the Synod of Bishops . - Mihály Laurinyecz (Warszawskie Studia Teologiczne, 2019)
The aim of this article is to analyse the events and documents of the Third Extraordinary General Assembly of the Synod of Bishops in 2014 and Fourteenth Ordinary General Assembly of the Synod of Bishops in 2015 in which Orthodox representatives also participated. It is commonly known that the Orthodox Churches allow divorced individuals to remarry and for remarried people to receive sacraments. In the present study we discuss who were present on behalf of the Orthodox Churches and sui iuris Eastern Catholics at the synod, what happened in relation to these denominations, and what references were made regarding Orthodox and Eastern practices and theology. First we look at the so-called “ordo” of the synods. Then we examine the preparatory documents in chronological order. After that we analyse the “Instrumentum laboris”. Following the analysis of the introductory document, the “Relatio ante disceptationem”, we summarise the activity of the so-called “circuli minores” based on the briefing reports. The entire extraordinary synod is summarised by the “Relatio synodi”, upon which the “Messaggio del Sinodo dei Vescovi al Popolo di Dio” is based. Finally we categorised the various issues discussed.